A study on the perception and acceptance of UiTM’s undergraduates towards open and distance learning method in Mandarin language teaching and learning during covid-19 movement control order period / Tay Yang Lian and Chin Jing Ru - Lian, Tay Yang; Ru, Chin Jing (Universiti Teknologi MARA, 2020)
The unexpected transformation from traditional face-to-face classes to Open and Distance Learning (ODL) mode, due to the implementation of Movement Control Order (MCO) caused by COVID-19 pandemic, has deeply affect the basic Mandarin learners in higher education institutes. After studying Mandarin level 1 through face-to-face classes for only three weeks, students were forced to adjust and adapt to ODL mode within a short amount of time. This situation would inevitably affect their learning quality and progress during the MCO period. Hence, a study on the students’ perception and acceptance towards ODL under this circumstance is crucial as a pilot test, to establish a better understanding on the possibility of ODL’s sustainability as a necessary component in learning Mandarin henceforward. Such study will also help to apprehend and further satisfy students’ requirement on studying Mandarin through ODL, so that it will become an ideal complement, or even a more preferred main option compared to the conventional teaching activities.